New curative approach using embolization followed by moderate-dose radiotherapy after surgical failure for large right heart metastasis. (January 2022) - Delanian, Sylvie; Awad, Sameh; de Gramont, Aimery
Highlights: Rapid improvement observed in a patient with a large cardiac metastasis. There is today no curative therapeutic option when the tumor is inoperable. Transcoronary tumor embolization plus moderate targeted radiotherapy should be a new option for tumor control. Abstract: Purpose: Cardiac metastasis is a rare fatal event. An intracavitary right tumor mainly in the ventricle is difficult to manage. Literature reports suggest that cardiac surgery in oligometastatic patients could offer median survival of 1 year. We investigated salvage treatment comprising transcoronary tumor embolization followed 15 days later by cardiac radiotherapy (40.5 Gy/15 fractions). Cases: We report two cases of severe right cardiac metastasis with a history of abdominal cancer managed by this salvage treatment following residual cardiac mass after previous cardiac surgery. Conclusion: Both symptomatic patients improved progressively and were locally controlled for at least 1 year without toxicity.